Establishing zakat on oil and gas in Malaysia: A new insight - Pg Mohd Faezul Fikri Ag Omar; Haneffa Muchlis Gazali; Mohd. Nasir Samsulbahri; Nurul Izzati Abd Razak; Norhamiza Ishak (ISRA International Journal of Islamic Finance, 2021)
Purpose - The purpose of this paper is to deliberate on the establishment of zakat (Islamic alms) on oil and gas in Malaysia. Being one of the five Islamic pillars, zakat contributes significantly to the country's socio-economic development and prosperity. However, in Malaysia and other Islamic countries, there is not yet a proper mechanism for calculating zakat on extracted minerals. Similar to gold and silver, oil and gas are valuable minerals, which, upon extraction, are subject to zakat payment. In Malaysia, however, this is not the case. Design/methodology/approach - This study uses a qualitative method. It presents a thorough review on the stipulation for paying zakat on minerals, specifically oil and gas. The deliberation is based on secondary data entailing a comprehensive content analysis of prominent books on the subject, current zakat rulings and legal acts on oil and gas. Findings - Oil and gas are subject to zakat payment, as indicated in several Qurʾānic verses and based on the academic reasoning of Muslim scholars. The zakat calculation for oil and gas entails the nisāb (minimum threshold value of the assets) but not the ḥawl (the requirement for one full Islamic year of ownership for the assets), by analogy with zakat on agricultural produce. Despite the obligation to pay zakat on minerals under the zakāt al-māl (alms due on wealth) category, oil and gas is yet to be fully subject to this practice in Malaysia, although the country is known as an oil-producing Muslim country. Several legislative acts covering the managerial and business side of oil and gas operations have long been established, but the provision on zakat remains unclear. Hence, comprehensive legislation is needed to fine-tune the Malaysian oil and gas system, particularly with regard to zakat. Research limitations/implications - This study relies mainly on secondary data and literature without performing any empirical investigations. Practical implications - In terms of academic implication, this study enriches the existing body of knowledge on zakat. Practical implications would include enhanced decision-making concerning zakat on oil and gas on the part of zakat institutions, policymakers and the government of Malaysia. Originality/value - This study provides practical and academic contributions to the deep understanding of zakat on oil and gas, which has received very little attention in the existing body of literature. Despite being limited in literature, this is a breakthrough study that sheds light on zakat on oil and gas.
Keywords: 330; Zakat; Oil and gas; Socio-economic development; Zakat collection; Zakat on minerals